From Participation to Legislative Knowledge: A Bibliometric Review of E-Participation Research in Legislative Institutions - Rahayu Yuni Susanti; Marimin; Dikky Indrawan; Nur Hasanah (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2026)
This study provides a comprehensive science map of e-Participation research in legislative institutions, addressing the fragmentation and lack of connection between citizen input and internal knowledge management. The purpose is to map the field's intellectual structure, evaluate the traceability of citizen inputs into parliamentary outputs, and identify strategic research gaps. Using the SPAR-4-SLR framework and PICOS-based screening, 41 empirical journal articles were selected from the Scopus database for bibliometric analysis using Bibliometrix and VOSviewer. Findings indicate that the field is dominated by European contexts and grounded in participation theory, institutional implementation, and behavioral adoption models. While recent trends show an increasing focus on advanced analytics and artificial intelligence, existing literature fails to explain how e-Participation mechanisms integrate with internal knowledge management. Specifically, there is no standardized metric to trace citizen input from initial submission to final committee recommendations or legislative amendments. This study contributes by offering an integrated scientific map tailored to legislative settings and proposing the Legislative Knowledge Transformation Model (LKTM). This model provides strategic guidance and practical indicators to strengthen evidence-based and transparent legislation. By establishing a reproducible pipeline for managing participatory data, the research paves the way for comparative validation in developing countries to enhance parliamentary oversight and institutional legitimacy.